Functional role of heritage and historical buildings in the city of salt at Jordan: perceptions of visitors and the local community - Aburumman, Asad H.; Al-Leheabi, Saleh Muhammad Zeki Mahmood (Al-Adab Journal, 2022)
This study aims to reveal the importance of the tangible historical heritage, especially the old heritage buildings, and how they can be reused and employed in suitable works for the history of these buildings. Therefore, this study focused on clarifying the functional role of the heritage buildings in the historic city of Salt in Jordan where there are many Heritage buildings in the city. They were used for many functions such as museums, restaurants and cafes. Therefore, the study focused on taking the opinion of visitors and the local community on the functional role of these buildings